An Intelligent Circular Economy Upstream Monitoring & Optimization System Based on Industrial Internet of Things - Anttila, Juha (My University, 2019)
Industrial Internet of Things (IIoT) has many beneficial applications upon the industry of Oil and Gas (O&G) and renewable energy production. Renewable energy production is already growing faster than traditional fossil fuel production. It has been estimated that the O&G sector can retain its current level of energy production for 40 years with the already discovered crude oil resources. In order to make sure that energy supply matches the demand, companies operating in the field of oil and gas are already heavily investing in energy efficiency, alternative energy processes and products. However, outdated technologies, legacy systems and prevailing conservative mindset hinder the development of the industry. This master’s thesis will be focused on the use of Industrial Internet of Things by the circular economy upstream which consists of data acquisition, analysis and visualization across the feedstock exploration and production phases in the field of oil and gas. New technologies such as cloud computing and analysis will be implemented to the current environment and further evaluated for the use of prevailing protocols such as OPC-UA which is the industry-leading communication protocol. The upstream sector will be evaluated for the purpose of designing, implementing and validating organization-wide system architecture model and experimental proof-of-concept level IIoT system for monitoring and optimization of the circular economy industry. The system will be evaluated and designed to support qualitative measurements such as a liquid fingerprint in the future. Considering the further use of the raw material, and based on the theoretical part of this thesis, an experimental prototype level IIoT system will be implemented and tested in practical terms. This thesis proves that the analyzed, designed, implemented and verified IIoT monitoring and optimization system has significant financial and environmentally beneficial results in the industry of the circular economy. This thesis proves that prevailing outdated systems can be further developed with modern technologies and solutions which are extensively described in the organization’s new system architecture model. The final conclusion indicates that Industry 4.0 and Industrial Internet of Things play a major role in the monitoring and optimization of the circular economy upstream industry.
Keywords: Industry 4.0, IoT, IIoT, AHP, Circular Economy, Upstream, System Requirement Analysis, RAMI 4.0, Ultrasonic, Arduino, Cloud, Microsoft Azure